Alkylbenzene synthesis from benzene and syngas over a ZnCrOx/beta bifunctional catalyst. Issue 6 (8th April 2022) - Liu, Jianchao; Xu, Hong; Dong, Jinxiang; Zhou, Ligong; Li, Xuekuan; Ge, Hui
Abstract : ZnCrOx/beta bifunctional catalyst. Abstract : The synthesis of alkylbenzenes produced from syngas and benzene over a ZnCrOx/beta bifunctional catalyst has been studied. Our characterization results showed that in the mixed catalyst the beta-zeolite crystallites were dispersed on the surface of the ZnCr oxides. The close contact facilitated the methanol intermediate formed on ZnCrOx to diffuse to the acidic sites of the beta-zeolite crystallites, reacting with benzene to produce alkylbenzenes. The competitive side reactions, which lead to by-products such as CO2 and hydrocarbons, were suppressed. The medium strong acidity and mesopores of the beta-zeolite crystallites contributed to the high activity and selectivity. The optimized ZnCrOx/beta-11 = 1 : 3 (w/w) afforded 40.72% benzene and 62.40% CO conversion with high alkylbenzene selectivity during the initial stage of the reaction, which then underwent quick deactivation, and maintained a benzene conversion of ∼27%. Coke formation on the beta-zeolite crystallites was proposed to be the main cause of deactivation.